Penerapan Pendekatan Komunikatif Pada Pembelajaran Bahasa Indonesia untuk Meningkatkan Pendidikan Karakter Pada Siswa Di SD Negeri 055983 Sei Mati Langkat - Siti Rahmawati; Dela Kurniati (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to improve student character education. This research is classroom action research (PTK) using a qualitative approach. The reason the researcher used the classroom action research method was to improve students' character through a communicative approach to language learning. This research was carried out at State Elementary School 055983 Sei Mati Langkat. The subjects in the research were 20 class IV students consisting of 13 female students and 7 male students. The research object is the communicative approach. Data collection techniques are observation and tests.